1993
DOI: 10.1136/jcp.46.6.564
|View full text |Cite
|
Sign up to set email alerts
|

Use of fine needle aspiration cytology for investigating lymphadenopathy in HIV positive patients.

Abstract: The cytological diagnoses of 27 lymph node aspirates were compared with the histological diagnoses or clinical outcome in 23 HIV positive patients. There was agreement between the cytological and histological diagnoses in 14 of the 16 surgically biopsied cases. The clinical outcome in the remaining 11 cases was consistent with the cytodiagnosis. Fine needle aspiration (FNA) is a reliable, miniimally traumatic, cost effective method with high specificity. It is suitable for an initial rapid diagnosis in HIV pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
5
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 3 publications
8
50
5
1
Order By: Relevance
“…This is comparable with what previous studies found. 13,18 This study had a lower false negative rate in TB diagnosis when compared to a study by Aljafari et al in Sudan where he found a false negative rate of 38% using a bigger gauge needle. 19 The difference, probably can be attributed to the differences in sizes of needles used, since the bigger the needle the higher the chances of haemorrhage distorting the cytological picture.…”
Section: Diagnostic Accuracymentioning
confidence: 49%
See 2 more Smart Citations
“…This is comparable with what previous studies found. 13,18 This study had a lower false negative rate in TB diagnosis when compared to a study by Aljafari et al in Sudan where he found a false negative rate of 38% using a bigger gauge needle. 19 The difference, probably can be attributed to the differences in sizes of needles used, since the bigger the needle the higher the chances of haemorrhage distorting the cytological picture.…”
Section: Diagnostic Accuracymentioning
confidence: 49%
“…This is comparable to the previous studies done. 13,18,26 Over a third of patients with lymphadenopathic KS (n=10), had mucocutaneous KS as well, which emphasizes the importance of examination of the skin and mucous membranes in HIV positive patients with lymphadenopathy, since it may elucidate on the possible cause of lymphadenopathy.…”
Section: Aetiology Of Cervical Lymphadenopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Bates et al 13 found reactive changes in 41% of HIV aspirates. Satyanarayana et al 14 reported a reactive cytomorphological pattern in 16.4% of their cases of tuberculosis, which is lower than our study.…”
Section: Reactive Lymphadenopathymentioning
confidence: 99%
“…Los datos recopilados en ellos son diversos y, en su mayoría, provienen de series de casos de adenopatías en pacientes sometidos a biopsia por aspiración con aguja fina en zonas de gran prevalencia de tuberculosis, como lo es nuestro país (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). No existe información sobre la frecuencia o la etiología en los pacientes con adenopatías en Colombia.…”
unclassified